The relationship between motivations and nurses' intention to share knowledge - Hamid Rafieian-Isfahani; Hamid-Reza Peikari; Mohsen Rafieyan-Isfahani (Wolters Kluwer Medknow Publications, 2020)
Background: This study intended to examine the association between the intrinsic and extrinsic motivation and knowledge sharing intentions among the nursing staff. Materials and Methods: It was a descriptive-correlational study, and the population included 860 nurses, working in Al-Zahra hospital, from whom a sample of 275 subjects were selected through convenience sampling method. The intrinsic motivation was composed of two sub-instruments, namely, the public recognition instrument (covering 3 items) and reciprocity instrument (covering 3 items), while extrinsic motivation included a knowledge self-efficacy instrument and an altruism instrument with 3 and 4 items, respectively. Moreover, knowledge sharing intention itself was evaluated a by 4-item inventory. Once the content validity, face validity, and construct validity (using confirmatory factor analysis), as well as the reliability (Cronbach's alpha) were confirmed, the model was analyzed through the partial least square technique. Results: There was a statistically significant association between both the intrinsic motivation and knowledge sharing intention (t = 14.95, p < 0.01,) and extrinsic motivation and knowledge sharing intention (t = 3.07, p < 0.01). Moreover, it was found that knowledge sharing intention was positively associated with public recognition (t = 3.98, p < 0.01), knowledge self-efficacy (t = 3.17, p < 0.01), and altruism (t = 11.44, p < 0.01). However, the association between the reciprocal benefits and intention to knowledge sharing was not supported (t = 1.77, p < 0.05). Conclusions: The results indicate that both intrinsic and extrinsic motivations, including public recognition, altruism, and knowledge self-efficacy perceptions can be used to encourage knowledge-sharing practices among the nurses.